Mechanistic attributes of S100A7 (psoriasin) in resistance of anoikis resulting tumor progression in squamous cell carcinoma of the oral cavity. Issue 1 (December 2015) - Dey, Kaushik; Sarkar, Siddik; Pal, Ipsita; Das, Subhasis; Dey, Goutam; Bharti, Rashmi; Banik, Payel; Roy, Joygopal; Maity, Sukumar; kulavi, Indranil; Mandal, Mahitosh
Abstract Background Squamous cell carcinoma of the oral cavity (SCCOC) is the dominant origin of cancer associated mortality. Previous findings by our study reported that acquisition of anoikis resistance has a significant role in tumor progression of oral cavity. Several genes were over-expressed in anoikis-resistant cells under detached conditions which we confirmed earlier by microarray. Normal oral squamous epithelia grow adherent to a basement membrane, and when detached from the extracellular matrix, undergoes programmed cell death. The acquisition of anoikis-resistance is crucial phenomena in oral tumor advancement. In the current study, we have identified S100A7 expression as contributing factor for anoikis resistance and tumorigenicity in human oral cancer cells. Further, we have explored that elevated S100A7 expression in anoikis-sensitive oral keratinocytes and cancer cells reshape them more resistant to anoikis and apoptosis inducers via activation of cellular intrinsic and extrinsic avenue. Methods A subset of human cancer cell lines TU167, JMAR, JMARC39, JMARC42 and MDA-MB-468 were utilized for the generation of resistant stable cell lines. Further, immunohistochemistry, western blot and immunoprecipitation, assays of apoptosis, soft agar assay, orthotopic animal model and signaling elucidation were performed to establish our hypothesis. Results S100A7 gene is found to be responsible for anoikis resistance and tumorigenicity in human oral cancer cells. We have observed up-regulation of S100A7 in anoikis resistant cell lines, orthotropic model and patients samples with head and neck cancer. It is also noticed that secretion of S100A7 protein in conditioned medium by anoikis resistant head & neck cancer cell and in saliva of head and neck cancer patients. Up-regulation of S100A7 expression has triggered enhanced tumorigenicity and anchorage-independent growth of cancer cells through Akt phosphorylation leading to development of aniokis resistance in head and neck cancer cells. Conclusions These data have led us to conclude that S100A7 is the major contributing factor in mediating anoikis-resistance of oral cancer cells and local tumor progression, and S100A7 might be useful as diagnostic marker for early detection of primary and recurrent squamous cell cancer.